2018
DOI: 10.1021/acsnano.7b09029
|View full text |Cite
|
Sign up to set email alerts
|

Strain Modulation by van der Waals Coupling in Bilayer Transition Metal Dichalcogenide

Abstract: Manipulation of lattice strain is emerging as a powerful means to modify the properties of low-dimensional materials. Most approaches rely on external forces to induce strain, and the role of interlayer van der Waals (vdW) coupling in generating strain profiles in homobilayer transition metal dichalcogenide (TMDC) films is rarely considered. Here, by applying atomic-resolution electron microscopy and density functional theory calculations, we observed that a mirror twin boundary (MTB) modifies the interlayer v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Both the moment method and the model‐based method require initial positions for the algorithm to proceed. However, determining the number of atomic columns is challenging in multiphase material systems, such as bilayer MoSe 2 with coexistence of 2H and 3R phases, due to the need to specify multiple sets of basis vectors in the preprocessing stage. Recently this problem has been overcome by successfully implementing Bayesian statistics to extract the optimal number of atomic columns and positions in low signal‐to‐noise ratio (SNR) STEM images .…”
Section: Atom Column Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the moment method and the model‐based method require initial positions for the algorithm to proceed. However, determining the number of atomic columns is challenging in multiphase material systems, such as bilayer MoSe 2 with coexistence of 2H and 3R phases, due to the need to specify multiple sets of basis vectors in the preprocessing stage. Recently this problem has been overcome by successfully implementing Bayesian statistics to extract the optimal number of atomic columns and positions in low signal‐to‐noise ratio (SNR) STEM images .…”
Section: Atom Column Detectionmentioning
confidence: 99%
“…In 2010, Krivanek et al successfully mapped out carbon and oxygen atoms in a monolayer boron nitride (BN) using STEM. Since then, a plethora of atomic defects in various 2D material systems under different growth conditions have been intensively studied . Atomically doped 2D transition metal dichalcogenides (TMDCs) with other transition metal or chalcogen atoms such as Mo x W 1‐x X 2 (X = S, Se) and MSe 2(1‐x) S 2x (M = Mo, W) have been reported to tune the bandgap of the alloy systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many studies have been reported on the strain effect of 2D layered materials [10][11][12]. This effect has been proved that the optical band gap can be tuned by up to several hundred meV/% in atomically thin TMDs by local strain [13].…”
Section: Introductionmentioning
confidence: 98%